The Role of Artificial Intelligence in Modern Medicine: Advancements, Applications, and Challenges - Tohirova Marjona Umidjon kizi (American Journal of Bioscience and Clinical Integrity, 2026)
Artificial Intelligence (AI) has emerged as a transformative force in contemporary healthcare, fundamentally reshaping diagnostic processes, therapeutic decision-making, and patient management systems. By leveraging machine learning algorithms, big data analytics, and computational modeling, AI enhances clinical accuracy and operational efficiency. This article critically examines the multifaceted role of AI in modern medicine, with particular emphasis on diagnostics, personalized treatment, surgical innovation, and disease prevention. Drawing upon recent empirical studies and real-world applications, the paper highlights both the opportunities and ethical challenges associated with AI integration. The findings suggest that, despite certain limitations, AI holds substantial potential to optimize healthcare delivery and improve patient outcomes on a global scale.